2018
DOI: 10.1055/s-0038-1636944
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Sinonasal Disease Foci: Do They Really Affect Mucosal Chronic Otitis Media?

Abstract: Background This study aimed to find the relationship between sinonasal predisposing foci in chronic otitis media mucosal disease (COMMD) and risk from these predisposing disease foci, and to identify the correlation of bacterial flora of the ear and nose in chronic otitis media. Materials and Methods This was a prospective case–control study with 100 cases and 100 controls. All patients underwent a detailed clinical ear-nose-throat (ENT) examination and diagnostic nasal endoscopy to look for sinonasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…10 As revealed in our previous study, even though a majority (> 90%) of the cases with COM have some or the other "predisposing disease focus" in the sinonasal region, it may not necessarily lead to an ET dysfunction. 9 Our data show that the ET function could get affected even in patients with traumatic TM perforation. This means that the ET dysfunction may not necessarily lead to COM all the times.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…10 As revealed in our previous study, even though a majority (> 90%) of the cases with COM have some or the other "predisposing disease focus" in the sinonasal region, it may not necessarily lead to an ET dysfunction. 9 Our data show that the ET function could get affected even in patients with traumatic TM perforation. This means that the ET dysfunction may not necessarily lead to COM all the times.…”
Section: Discussionmentioning
confidence: 57%
“…Many times, it is difficult to distinguish a physiological structure such as an anatomical variation from a definitive pathological focus in the nose and paranasal sinuses, as revealed in our previous study. 9 Also, it is difficult to establish to what extent the disease focus directly or indirectly affects the functioning of the ET. It has been shown that there is a tendency for poor ET function in patients with nasal septal deviation.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our own previous studies, we have discovered that the adenoids could pose a considerable risk factor for the development of chronic otitis media. 1 This paper aimed to study the clinicopathological features of persistent adenoids and their secondary effects on the upper respiratory tract.…”
Section: Introductionmentioning
confidence: 99%